Landscape features impact connectivity between soil populations: a comparative study of gene flow in earthworms. Issue 12 (3rd April 2017) - Dupont, L.; Torres‐Leguizamon, M.; René‐Corail, P.; Mathieu, J.
Abstract: Landscape features are known to alter the spatial genetic variation of aboveground organisms. Here, we tested the hypothesis that the genetic structure of belowground organisms also responds to landscape structure. Microsatellite markers were used to carry out a landscape genetic study of two endogeic earthworm species, Allolobophora chlorotica ( N = 440, eight microsatellites) and Aporrectodea icterica ( N = 519, seven microsatellites), in an agricultural landscape in the North of France, where landscape features were characterized with high accuracy. We found that habitat fragmentation impacted genetic variation of earthworm populations at the local scale. A significant relationship was observed between genetic diversity ( H e, A r ) and several landscape features in A. icterica populations and A. chlorotica . Moreover, a strong genetic differentiation between sites was observed in both species, with a low degree of genetic admixture and high F st values. The landscape connectivity analysis at the regional scale, including isolation by distance, least‐cost path and cost‐weighted distance approaches, showed that genetic distances were linked to landscape connectivity in A. chlorotica . This indicates that the fragmentation of natural habitats has shaped their dispersal patterns and local effective population sizes. Landscape connectivity analysis confirmed that a priori favourable habitats such as grasslands may constitute dispersal corridors for these species.